Analisis Faktor Yang Mempengaruhi Disiplin Kerja Pegawai Di Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Aceh Tamiang - Salsabila Khalisa; Muhammad Rizqi Zati; Dhian Rosalina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the effect of workload and work conflict on work discipline among employees at the Aceh Tamiang BKPSDM. This study uses quantitative methods with the help of the SPSS Version 26 application. The analytical method used is multiple linear regression method. The sample in this study was 42 people, using the saturated sampling method, so that all populations were used as samples. The reason for all employees being sampled is because each employee has a different personality and assessment. In this study data collection used interview techniques and questionnaires, in which the questionnaires had been tested for validity and reliability tests. The results of this study show the equation Y = 153.986 - 0.460X1 - 0.351X2. The result of the t test for the effect of workload (X1) on work discipline (Y) is 0.013 ˂ 0.05. The result of the t test for the effect of work conflict (X2) on work discipline (Y) is 0.037 ˂ 0.05. The results of the F test for the simultaneous effect of workload (X1) and work stress (X2) on work discipline (Y) are 0.013 ˂ 0.05. Workload has a significant effect on work discipline, work conflict has a significant effect on work discipline and workload and work conflict simultaneously have a significant effect on work discipline.